2019
DOI: 10.3390/molecules24101908
|View full text |Cite
|
Sign up to set email alerts
|

Arnicolide D, from the herb Centipeda minima, Is a Therapeutic Candidate against Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is a high morbidity and mortality cancer with an obvious racial and geographic bias, particularly endemic to Southeast China. Our previous studies demonstrated that Centipeda minima extract (CME) exhibited anti-cancer effects in human NPC cell lines. Arnicolide C and arnicolide D are sesquiterpene lactones isolated from Centipeda minima. In this study, for the first time, we investigated their anti-NPC effects and further explored the related molecular mechanisms. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…The whole plant has been employed as a TCM for millennia and is commonly treatment for indications such as rhinitis, sinusitis, cough, headache, swelling, and allergy (11). Phytochemical research has demonstrated CM mainly contain phenolic acids (e.g., isochlorogenic acid A and isochlorogenic acid C), flavonoids, and sesquiterpene lactones [e.g., Brevilin A, Arnicolide D; (12)(13)(14)(15)(16)]. Reports suggest that Centipeda minima extracts (CME) possess anti-inflammatory (17), anti-bacterial (18,19), and anti-allergic (20) effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole plant has been employed as a TCM for millennia and is commonly treatment for indications such as rhinitis, sinusitis, cough, headache, swelling, and allergy (11). Phytochemical research has demonstrated CM mainly contain phenolic acids (e.g., isochlorogenic acid A and isochlorogenic acid C), flavonoids, and sesquiterpene lactones [e.g., Brevilin A, Arnicolide D; (12)(13)(14)(15)(16)]. Reports suggest that Centipeda minima extracts (CME) possess anti-inflammatory (17), anti-bacterial (18,19), and anti-allergic (20) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Reports suggest that Centipeda minima extracts (CME) possess anti-inflammatory (17), anti-bacterial (18,19), and anti-allergic (20) effects. Previous studies have demonstrated the anti-cancer effects of CME, and compounds extracted from CM, in various cancers including nasopharyngeal carcinoma (13,14,21,22), leukemia (23), glioblastoma (24), lung cancer (25), and colon cancer (26), however, the effects of CME on breast cancer have to date, not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…International Publisher effects, in cancers including colon carcinoma [10], melanoma [11], and nasopharyngeal carcinoma [12]. However, there have been no reports on the effects of AD in TNBC.…”
Section: Ivyspringmentioning
confidence: 99%
“…Thus, natural products are attracting increasing amounts of attention from researchers in the cancer field. Arnicolide D (AD) (Figure 1 ), a natural sesquiterpene lactone extracted from Centipeda minima 9 , has been reported to exhibit anti-bacterial 9 and anti-cancer effects, in cancers including colon carcinoma 10 , melanoma 11 , and nasopharyngeal carcinoma 12 . However, there have been no reports on the effects of AD in TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has recently been reported that certain phytochemical constituents of CMX have potential utility for the development of anticancer agents [3]. For example, arnicolide D isolated from CMX has been demonstrated to have anticancer effects against human nasopharyngeal carcinoma cells [4]. Previous studies have also reported that brevilin A, of which CMX is an abundant source, shows anticancer effects on a range of different cancer cell lines, including those of lung, breast, liver, and colon cancers and melanoma [5][6][7].…”
Section: Introductionmentioning
confidence: 99%